Analisis Pemanfaatan Tren Visual Kampanye Media Luar Ruang Pada Pemilu 2024 di Banda Aceh - Novi Susilawati; Annisah Putri; Nurul Fajri; Maghfira Faraidiany (INDO PUBLISHING, 2026)
The democratic principles that underpin the implementation of elections in Indonesia create space for freedom of expression, including in political campaigns. The 2024 general election in Banda Aceh showcases campaign strategies through outdoor media, such as billboards and banners, which line almost every street with attractive designs and text. Many of these campaign banner designs feature modern visuals and language, seemingly aimed at specific voter segments. This study focuses on Gen Z voters, as there is a noticeable phenomenon that Gen Z is highly exposed to outdoor campaign media. The purpose of this study is to explore the extent to which visual elements in outdoor campaigns can capture the attention of Gen Z voters. This research is descriptive and analytical in nature. Data collection was carried out through interviews to gain insights into individuals' perspectives and experiences related to the presence of outdoor campaign media. Although Gen Z is the dominant user of technology and digital platforms, the presence of billboards as a physical outdoor medium remains effective in capturing their attention.